2017
DOI: 10.1515/enr-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

The role of thyrostimulin and its potential clinical significance

Abstract: Th yrostimulin is a glycoprotein heterodimer of GPA2 and GPB5, fi rst described in 2002. It is involved in the physiological function of several tissues. Moreover, evidence points towards the ability of thyrostimulin's individual monomers to induce a biological eff ect, which could denote the circulatory/systemic eff ects of the molecule when found in higher concentrations. From the evolutionary point of view, thyrostimulin shares a binding epitope with the thyroid-stimulating hormone for the thyroid stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…This suggests an increased metabolic rate in GHSR-KO mice, as even a onedegree increase in body temperature could thermodynamically correspond with a ten-percent rise in metabolic rate [30]. Thus, in a similar way to other hormones in animals, ghrelin may play a role in metabolism regulation, resulting in energy expenditure decrease through decreased thermogenesis [31]. However, the mice in this study were of global GHSR-knockout and is thus of limited specificity.…”
Section: Ghrelin and Adipositymentioning
confidence: 79%
“…This suggests an increased metabolic rate in GHSR-KO mice, as even a onedegree increase in body temperature could thermodynamically correspond with a ten-percent rise in metabolic rate [30]. Thus, in a similar way to other hormones in animals, ghrelin may play a role in metabolism regulation, resulting in energy expenditure decrease through decreased thermogenesis [31]. However, the mice in this study were of global GHSR-knockout and is thus of limited specificity.…”
Section: Ghrelin and Adipositymentioning
confidence: 79%
“…The mechanism of action and physiological consequences of thyrostimulin remain largely unknown, and because a de facto thyrostimulin has yet to be extracted from blood or tissue, recombinant proteins have been used to characterize all binding, reporter, and in vivo / in vitro studies [5, 6, 10, 42, 54]. A wide range of potential physiological functions have been implicated for thyrostimulin, including cancer, immunity, and reproduction (reviewed in [60]). While thyrostimulin is hypothesized to be one of two pituitary GpHs in sea lamprey that function in an endocrine manner [11, 12, 47], there is no apparent conserved endocrine role in the elephant shark or mammals [6, 10].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we previously showed that TSHR couples to G q to activate phospholipase C to stimulate inositol-1,4,5-trisphosphate production with a 100-fold lower potency (EC 50 ) for TSH compared with G s activation (Allen et al, 2011). We found that activation of HEK 293 cells stably expressing the TSHR (HEK-TSHR cells) with TSH and thyrostimulin (a second TSHR cognate ligand) (Nakabayashi et al, 2002;Karponis and Ananth, 2017) exhibits IUDRC regulation of cAMP production. We show that this biphasic regulation occurs via activation of G s at low doses and by G i/ G o at high doses of TSHR ligands.…”
Section: Introductionmentioning
confidence: 99%